Impact of metal contamination to the emergence of (multi) antibiotic resistant bacteria in Thai Nguyen, Vietnam - Hoang Nam, Pham; Quang Huy, Nguyen; Thi Thu Hang, Le; Thy Ngoc, Nguyen; Thi Kieu Oanh, Nguyen; Van Hoi, Bui; Ngoc Lien, Nguyen; Thi Thu Hien, Nguyen; Mai Huong, Le; Dinh Luyen, Nguyen; et al. (Vietnam Journal of Biotechnology, 2022)
Heavy metal contamination in the environment due to anthropogenic activities in industrial and agricultural areas represents stress for the living ecosystem including soil microorganisms. The adaptive response of bacterial communities to these pollutants can be observed through the increasing proportion of resistant bacteria. Our study aimed at evaluating the effect of metal contamination to the emergence of bacteria resistant to 3 common antibiotics, ie., gentamycin, sulfamethoxazole, and norfloxacin in Tan Long Pb-Zn mining site, Thai Nguyen province by a culture-dependent approach. The results showed that under moderated Pb contamination, a significant increase in prevalence of gentamycin-resistant bacteria was observed. Antibiotic susceptibility test showed 45% of isolates resistant to at least two antibiotics among gentamycin, norfloxacin, tetracyclin, imipenem, andsulfamethoxazole, and 10.4 % of isolates resistant tho three antibiotics. More detailed investigations in molecular analysis are needed to identify and genetically characterize of multi-drug resistant isolates as well as to better understand the link between metal resistance and (multi)resistance to antibiotics.